Antibiotic resistance of Salmonella enterica strains isolated from guinea pig carcasses in a market in Lima, 2021 - Mansilla Q., Mariana (2023)
The aim of this study was to identify the antibiotic resistance of Salmonella enterica isolates from 384 samples of guinea pig carcasses from a market in Lima, Peru. The samples were inoculated in enrichment broth and cultured in specific media. Bacterial identification was performed using biochemical tests and antibiotic resistance using the plaque diffusion method against 16 antibiotics. Results showed that 28.9 ± 4.5% (111/384) of samples were positive for Salmonella enterica strains. Besides, 84.7% (94/111) showed resistance to at least one of the 16 antibiotics while 15.3% (17/111) were sensitive to all antibiotics. Likewise, 40.5% (45/111) of the strains showed multidrug resistance (MDR) to three or more antibiotics. The results confirm the risk that the commercialization of guinea pig carcasses contaminated with strains of Salmonella enterica resistant to antibiotics represents for public health.